107k views
2 votes
I have an interesting intergral that seems pretty challenging. After attempting to solve it for some time, I've come up empty handed. Can you solve this integral?

Indefinite Integral of:

{x}^(4) { {e}^(x) }^(3)


1 Answer

0 votes

Answer:


\displaystyle \int {x^4e^\big{x^3}} \, dx = \sum^(\infty)_(n = 0) (x^(3n + 5))/((3n + 5)n!) + C


\displaystyle \int {x^4e^\big{x^3}} \, dx = (\Gamma ((5)/(3), \ -x^3))/(3) + C

General Formulas and Concepts:

Calculus

Differentiation

  • Derivatives
  • Derivative Notation

Basic Power Rule:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Integration

  • Integrals
  • [Indefinite Integrals] Integration Constant C

Integration Property [Multiplied Constant]:
\displaystyle \int {cf(x)} \, dx = c \int {f(x)} \, dx

U-Substitution

Sequences

Series

Taylor Polynomials and Approximations

  • MacLaurin Polynomials
  • Taylor Polynomials

Power Series

  • Power Series of Elementary Functions
  • Taylor Series:
    \displaystyle P(x) = \sum^(\infty)_(n = 0) (f^n(c))/(n!)(x - c)^n

Integration of Power Series:


  1. \displaystyle f(x) = \sum^(\infty)_(n = 0) a_n(x - c)^n

  2. \displaystyle \int {f(x)} \, dx = \sum^(\infty)_(n = 0) (a_n(x - c)^(n + 1))/(n + 1) + C_1

Multivariable Calculus

Gamma Functions


  • \displaystyle \Gamma (s, x) = \int\limits^(\infty)_x {t^(s - 1)e^(-t)} \, dt
  • Incomplete Gamma Functions

Explanation:

*Note:

If we are talking single-variable calculus, then we would have to write this integral as a power series.

  • You can derive the power series for eˣ using Taylor Polynomials (not shown here)

If we are talking multi-variable calculus, then we could integrate this and get an "actual" value.

Single-variable Calculus

We are given the integral:


\displaystyle \int {x^4e^\big{x^3}} \, dx

We know that the power series for
\displaystyle e^x is:


\displaystyle e^x = \sum^(\infty)_(n = 0) (x^n)/(n!)

To find the power series for
\displaystyle e^\big{x^3} , substitute in x = x³:


\displaystyle e^\big{x^3} = \sum^(\infty)_(n = 0) ((x^3)^n)/(n!)

Simplify it, we have:


\displaystyle e^\big{x^3} = \sum^(\infty)_(n = 0) (x^(3n))/(n!)

Rewrite the original function:


\displaystyle \int {x^4e^\big{x^3}} \, dx = \int {x^4 \sum^(\infty)_(n = 0) (x^(3n))/(n!)} \, dx

Rewrite the integrand by including the x⁴ in the power series:


\displaystyle \int {x^4e^\big{x^3}} \, dx = \int {\sum^(\infty)_(n = 0) (x^(3n + 4))/(n!)} \, dx

Integrating the power series, we have:


\displaystyle \int {x^4e^\big{x^3}} \, dx = \sum^(\infty)_(n = 0) (x^(3n + 5))/((3n + 5)n!) + C

Multivariable Calculus

Let's set our variables for u-substitution:

u = x⁵ → du = 5x⁴ dx

Use u-substitution on the integral to obtain:


\displaystyle \int {x^4e^\big{x^3}} \, dx = (1)/(5)\int {e^\big{u^{(3)/(5)}}} \, dx

We see that the integral is an incomplete gamma function:


\displaystyle \int {x^4e^\big{x^3}} \, dx = (1)/(5) \bigg[ \frac{5 \Gamma ((5)/(3), \ -u^\big{(3)/(5)})}{3} \bigg] + C

Simplifying it, we have:


\displaystyle \int {x^4e^\big{x^3}} \, dx = \frac{\Gamma ((5)/(3), \ -u^\big{(3)/(5)})}{3} + C

Back-substituting u will give us the final result:


\displaystyle \int {x^4e^\big{x^3}} \, dx = (\Gamma ((5)/(3), \ -x^3))/(3) + C

User Keith Smiley
by
4.9k points